Abu Yusuf Ya‘qub ibn Ishaq Al-Kindi - Cheema, Asma Naseer (International Journal of Pathology, 2018)
Under the influence of final divine book Quran e majeedand explanations through acts and words of final Prophet ofAllah Muhammad p.b.u.h. Sciences progressed with jetspeed. The great emphasis on learning, research, honesty,hard work and lack of biases & greed provided the mostoptimum and fertile soil for growth of sciences and scientists.Numerous outstanding scientists were born in the mostglittering civilization under Muslim dominance!